MONETARY VALUATION BY APPLYING PENALTY RATE ON BIRD POPULATION AT KENYIR LAKE RAINFOREST, MALAYSIA - Jaafar M.N.; Malek M.A.; Salim J.M. (Universiti Malaysia Terengganu, 2023)
A variety of methods have been used by researchers to monetise the value of birds in the forest ecosystem. In this study, a valuation method based on fines and penalty rate imposed on poachers or individuals who commit offenses that contribute to the destruction of wildlife of birds listed under Malaysia Wildlife Conservation Act 2010 has been used to estimate monetary value of bird population study conducted at Kenyir rainforest. For the purpose of this study, secondary data on bird population recorded at Kenyir rainforest was used. The result suggests that monetary value of birds in the study area was estimated to be in the MYR 2.07 million to MYR 6.9 million range. The exercise of converting the direct value of birds in monetary terms is important to assist in the determination of the value of wildlife in the eyes of the Malaysian law and its people to make them more appreciative of the value of wildlife in the forest ecosystem. 2021 Penerbit UMT. All Rights Reserved.